Clinico-epidemiological Analysis of Stenotrophomonas maltophilia Bacteraemia, its Associated Risk Factors and Outcome in Patients Admitted at a Tertiary Care Centre in Northern India- A Retrospective Cohort Study - Romya Singh; Mitra Kar; Akanksha Dubey; Chinmoy Sahu; Sangram Singh Patel (National Journal of Laboratory Medicine, 2024)
Introduction: Stenotrophomonas maltophilia is a Gram-negative, motile, and glucose non fermenting bacterium commonly found in hospital settings. It poses a significant risk to immunocompromised individuals, often causing nosocomial infections. Aim: To identify the risk factors associated with Stenotrophomonas maltophilia bacteraemia and compare the factors influencing patient survival and mortality. Materials and Methods: Clinical and laboratory data from 39 cases of Stenotrophomonas bacteraemia encountered between July 2021 and July 2022 in the Department of Microbiology, Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, Uttar Pradesh, India, were analysed in the present retrospective study in August 2022. The study included all cultures positive for S. maltophilia bacteraemia, identified through Matrix-assisted Laser Desorption Ionisation Time-Of-Flight Mass Spectrometry (MALDI-TOF-MS). Antibiotic susceptibility testing was performed using the Kirby-Bauer disk diffusion method, following the Clinical and Laboratory Standards Institute (CLSI) guidelines. Statistical analysis and outcome assessment were conducted using Statistical Package for Social Sciences (SPSS) version 20.0. Results: Clinical data from all 39 bacteraemia patients were extracted from the hospital information system for analysis. The mean age of the patients included in the present study was 46.0±20.29 years, with a male predominance of 27 (69.23%). The most common risk factors associated with S. maltophilia bacteraemia were the presence of an indwelling catheter in 21/39 cases (53.8%) and co-existing pulmonary infections in 18/39 cases (46.2%). S. maltophilia isolates exhibited high susceptibility to Minocycline (94.87%), Ticarcillin-Clavulanic acid (87.18%), Levofloxacin (84.62%), and Cotrimoxazole (84.62%). The 30-day mortality rate was reported as 28.20% (11/39). Conclusion: S. maltophilia can cause various infections in immunocompromised patients. The appropriate use of empirical antibiotics and strict adherence to infection control measures can reduce hospital stays, as well as 14-day and 30-day mortality rates among affected patients.